Ambient intelligence and intelligent environments for managers’ work support - MIKULECKY, Peter (Annals of Spiru Haret University. Economic Series, 2010)
One of the most developed and evolving areas promising for the future, which is already recently a subject of intensive research, seems to be the area of ambient intelligence. We present some recent results and contemplations about how this area could be exploited also for creating intelligent environments capable of managerial work support. Besides some general discussion we present also some of our views on the privacy concept which seems to be especially delicate in relation to the intelligent environments concept. Some notes about possible positive social acceptance of this phenomenon are concluding this work.